Strategies for bean production: An agricultural extension manual for the eastern region of the Democratic Republic of Congo - Kinyua, Michael; Waswa, Boaz; Rubyogo, Jean Claude; Mutambu, Dominic; Mandlenkosi, Nkomo; Kalemera, Sylvia; Ntukamazina, Nepomuscene; Mulonda, Lydie; Kihara, Job (2025)
The work on beans at the Alliance of Bioversity International and CIAT is supported by diverse funding partners. This work is implemented under the Pan-Africa Bean Research Alliance (PABRA) in collaboration with INERA and One CGIAR initiatives: the Sustainable Farming Program (SFP) building on investments by Excellence in Agronomy (EiA).